SPEECH IS AN IMPORTANT TOOL IN DEVELOPING STUDENTS' THINKING (Analysis of International Sciences, 2024)
Speech is not only a means of expressing an idea, but also a tool for its formation. Thought serves as the psychological basis of speech, and the condition for its growth is the enrichment of thought. It is possible to successfully develop speech only on the basis of mastering the system of mental activity. Therefore, great importance is attached to the preparation, improvement of the material, the selection, placement and logical operations of the material in the development of students' speech.